2012
DOI: 10.1177/0954411912445841
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasound-based measurement of tendon velocity and displacement for application toward detecting user-intended motion

Abstract: The motivation of this research is to non-invasively monitor the wrist tendon's displacement and velocity, for purposes of controlling a prosthetic device. This feasibility study aims to determine if the proposed technique using Doppler ultrasound is able to accurately estimate the tendon's instantaneous velocity and displacement. This study is conducted with a tendon mimicking experiment consisting of two different materials: a commercial ultrasound scanner, and a reference linear motion stage set-up. Audio-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…11,12 Researchers and clinicians have also used commercial ultrasound scanners with pulsed-wave Doppler and color Doppler imaging functions to quantify tendon displacement and velocity. 13 However, previous studies that used Doppler-based techniques to estimate tendon displacements found them to be effective only when the tendon velocity was higher than 25 mm/s. 13 This limitation means that Doppler imaging is not an effective tool for patients with tendon injuries, since the tendon velocity in such patients is normally below 25 mm/s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Researchers and clinicians have also used commercial ultrasound scanners with pulsed-wave Doppler and color Doppler imaging functions to quantify tendon displacement and velocity. 13 However, previous studies that used Doppler-based techniques to estimate tendon displacements found them to be effective only when the tendon velocity was higher than 25 mm/s. 13 This limitation means that Doppler imaging is not an effective tool for patients with tendon injuries, since the tendon velocity in such patients is normally below 25 mm/s.…”
Section: Introductionmentioning
confidence: 99%
“…13 However, previous studies that used Doppler-based techniques to estimate tendon displacements found them to be effective only when the tendon velocity was higher than 25 mm/s. 13 This limitation means that Doppler imaging is not an effective tool for patients with tendon injuries, since the tendon velocity in such patients is normally below 25 mm/s.…”
Section: Introductionmentioning
confidence: 99%